Produção de saúde e práticas de cuidado entre os Kaiowa em Mato Grosso do Sul - Moretti, Leandro Lucato (2022)
This research was built together with the Kaiowá people, a Guarani group from the southern region of the state of Mato Grosso do Sul. The context of the region is sharped by political projects of the non-indigenous society, the Karaí, based on economic activities, the so-called agribusiness. This form of production, which aims to generate profits, demands a wide occupation of land, and puts pressure on the Kaiowa territories, which are increasingly populous, and do not guarantee the necessary conditions for the reproduction of their ways of life and social organization. It is from this that arises the need for psychology to be an ally of the Kaiowa, and indigenous peoples in general, in their struggles to guarantee their rights, territories, strengthening their ways of life and knowledge. The present research aimed to investigate, identify, and dialogue with the production of health and care among the Kaiowa in MS, analyzing the conceptions of person and subjectivity that are related. Specifically, we sought to identify and describe care practices that they resort to and that they activate when they consider it necessary, in what are denominated cases of mental health; How they identify possible injuries or illnesses and how they classify ways of acting that are seen negatively; how they build therapeutic itineraries, which involves at the same time, their own practices and available indigenous health equipment. To achieve this objective, I chose to use the ethnographic method, building a dialogue between categories of social psychology socio-historical and anthropology, allowing us to link the themes that are the focus of this research: production of health and care, and indigenous mental health, from different perspectives, trying to build good relationships with kaiowa knowledge. That way, data and information were obtained through participant observation, resulting in approximations with the dynamics of knowledge production and social organization of these peoples, considering their perspectives and categories in their centrality. In this way, it is observed that the Kaiowa produce their own way of conceiving what we non-indigenous people conventionally call psychology, from which they will explain the processes of construction of people, bodies and subjectivities, using native categories based on their support networks and knowledge sets. Which allows us to conclude that the ability to produce care practices and organize their systems of knowledge about health, to give answers to questions they consider problematic, constantly elaborated and re-elaborated, are considered a capacity for resistance and a refusal in the face of constant actions of colonial forces that seek to normalize kaiowa life